Changes in multidisciplinary team decisions in a high volume head and neck oncological center following those made in its preferred partner - Hendrickx, Jan-Jaap; Mennega, Tommy; Uppelschoten, Jeroen M.; Leemans, C. René (Frontiers in Oncology, 2023)
Objective: Head and neck cancer care is highly complex, and multidisciplinary team meetings (MDTs) are vital for improved outcomes. In the Netherlands, head and neck cancer care is practiced in eight high-volume head and neck oncologic centers (HNOC) and six affiliated hospitals preferred partner (PP) centers. Patients treated in the PP are presented and discussed in the HNOC. To evaluate the importance of these mandatory and decisive steps in decision making, we have assessed the changes in treatment.Retrospective evaluation of head and neck cancer patients referred between January 2011 and October 2018 for a MDT evaluation to the HNOC was conducted. The differences in MDT recommendation were classified with regards to major and minor changes.Results: Management recommendation(MR) changed after 113 of 515 MDT discussions within the PP (487 patients; 22%), of which 86 cases (16%) were major changes. In 67 cases (59.3%), escalation of management was recommended, while in 43 cases (38.1%) de-escalation was recommended.There was a high rate of change of MRs, when comparing the PP recommendations with the HNOC recommendations. Since patient and tumor characteristics seem unable to predict these changes, we recommend all patients be seen for a clinical presentation, revision of diagnostics, and MDT discussion in a high volume HNOC.